Queering the Asian Diaspora - Bao, Hongwei (SAGE Publications, 2024)
The current COVID-19 pandemic has exuberated global geopolitical tensions and led to rising Sinophobia and anti-Asian racism worldwide. At the same time, there has been a nascent Asian diaspora consciousness emerging in the West, celebrating Asian identity and cultural heritage. In the space between anti-Asian racism and Asian Pride, LGBTQ+ people’s voices are largely missing. Can queer Asian diaspora comfortably identify with mainstream Asian diaspora and LGBT politics? Is a queer Asian diaspora cultural politics possible? What would it look like? This book answers these questions by drawing on a range of contemporary case studies from queer Asian diaspora cultural production in recent years including art, performance, film and political activism. Situated at the intersections of queer studies, diaspora studies and Asian Studies, this book articulates an intersectional cultural politics that is anti-racist, decolonial, anti-nationalist, feminist and queer.
paperback isbn